Temperature-dependent electrical transport characteristics of p-SnS/n-WO3:Sb heterojunction diode - T Gaewdang; Ng Wongcharoen (My University, 2018)
The p-SnS/n-WO3:Sb heterojunction diode was successfully obtained by thermal evaporating SnS thin films on WO3 doped with 2.0 mol% Sb2O3 of 1 mm thick ceramic pellet substrate. The electrical properties of p-SnS/n-WO3:Sb heterojunction were investigated by forward current–voltage–temperature (I–V–T) characteristics in the temperature range of 20-300 K. It was found that at low forward bias voltage (<0.25V), the conduction mechanism of the diode exhibits Ohmic conduction. At intermediate voltage (0.25<V<1.0V), the conduction mechanism is dominated by thermionic emission (TE). At bias voltage above 1.0 V, the current transport is due to space charge limited current (SCLC) controlled by an exponential trap distribution in the band gap of WO3:Sb. The temperature dependence of the saturation current and ideality factor are well described by tunneling enhanced recombination model occurring at junction interface with Ea and E00 values about 1.565 eV and 99.5 meV, respectively.
Keywords: Thermionic emission; Ohmic contact; Saturation current; Atmospheric temperature range; Semiconductor materials and interfaces